Freedom and religion in Kant and his immediate successors : the vocation of humankind, 1774-1800 - Di Giovanni, George, 1935- (Cambridge University Press, 2005)
"The theologians of the late German Enlightenment saw in Kant's Critique of Pure Reason a new rational defense of their Christian faith. In fact, Kant's critical theory of meaning and moral law totally subverted the spirit of that faith." "This new study examines the contribution made by the Critique of Pure Reason to this change of meaning. George di Giovanni stresses the revolutionary character of Kant's critical thought but also reveals how this thought was being held hostage to unwarranted meta-physical assumptions that caused much confusion and rendered the first Critique vulnerable to being reabsorbed into modes of thought typical of Enlightenment popular philosophy."--Jacket